Analysis of the Level Anxiety Related to the Self Efficacy of Eldelry with Hypertention - Tiveni, Elisabhet (GLOBAL HEALTH SCIENCE GROUP, 2024)
Aging is something that occurs biologically in each individual and causes a decrease in the functioning of the body’s organs, leading to chronic diseases, including hypertension. Hypertension will have psychological consequences for the elderly, the problem that often occurs is anxiety. Anxiety is a feeling of anxiety experienced by people about problems that do not necessarily occur. In addition to anxiety, other psychological problems that occur are self-efficacy or self-confidence and the ability of the person to solve the problems that arise. This study aims to determine the relationship between anxiety levels and self-efficacy in elderly people with hypertension. This research used a correlational descriptive design with a cross-sectional approach with 40 elderly respondents total sample. The entire population who suffer from hyepertention is 40 elderly and the entire population became respondents in this study and then data were collected using two questionaires, the Hamilton Anxiety Rating Scale (HARS) questionnaire to measure anxiety levels and the General Self Efficacy Questionaire (GSS) to measure levels of self efficacy elderly, the data are taken at the same time. There is a relationship between anxiety levels and self-efficacy in elderly people with hypertension, proven by the p-value of 0.000. The existence of psychological problems in the elderly, namely anxiety, can cause interference with the self-efficacy of the elderly, the elderly who have high levels of anxiety will tend to have low self-efficacy.